ANALISIS DEL PROBLEMA DE INTRUSION MARINA DEL ACUIFERO DE CHILCA MEDIANTE MODELAMIENTO NUMERICO - Sarango J., Douglas D. (2006)
The project has as objectives the analysis and evaluation of the nowadays problem given by the marine intrusion in the Chilca aquife, this will be done through numeric modeling. of the aquifer. In order to fulfill these objectives it is necessary to count with an appropriate handling of this aquifer system. Also it will be necessity to establish policies of operation, handling and conservation. In order to do so, a study of the spatial and temporal should be affected on this water resource. The numeric modeling of the Chilca aquifer has been affected under permanent regimen through the solution of the underground water flux equations for porous environment. The finite elements technique with the use of triangular nets was used, this was developed on the Micro Fem V.3 model. 143 triangular nets and 100 nodes were generated, given to each element data of water level, exploitation flow, transmissivities, etc. With the numeric calibrated model, the future exploitation hypothesis were simulated which were given by the agriculture sector. Through this, it was determinated the way for the new underwater level position on the area of Chilca aquifer. The sweet water / salt water interface location represents the marine intrusion problem. It was determinated applying the Ghyben-Herzberg conditions to the results from the new underground water levels obtained by la simulating the given exploitation hypothesis. The results indicate that the zones denominated S2, S3, S4, S5 and S6 on the valley of Chilca, the wells locate on the mentioned zones shall extract contaminated water with high sodium chloride content. Meanwhile, the S1 zone could only be exploited through wells in order to supply potable water to the city of Chilca located in the middle of the valley.